A new ENG mutation in a Japanese family with hereditary hemorrhagic telangiectasia and pulmonary arteriovenous malformations - Keiki Yokoo; Gen Yamada; Hirofumi Chiba; Aki Ishikawa; Hiroko Morisaki; Hiroshi Saijo; Sayaka Kudoh; Yasuo Kitamura; Naoki Hirokawa; Masahiro Miyajima; Atsushi Watanabe; Hiroki Takahashi (Respiratory Medicine Case Reports, 2018)
We present a case series of four siblings with hereditary hemorrhagic telangiectasia (HHT) and pulmonary arteriovenous malformations (PAVM). The patients' mother has HHT. Case 1: A 22-year-old man developed dyspnea and epistaxis. CT revealed a large PAVM, treated by segmentectomy. Case 2: A 27-year-old woman developed epistaxis and dyspnea. CT revealed three PAVMs, treated by partial resection. Case 3: A 20-year-old woman developed dyspnea. CT revealed multiple PAVMs, treated with endovascular occlusion of the largest one. Case 4: A 12-year-old woman developed epistaxis. CT revealed multiple PAVMs, observed without treatment. Genetic testing identified a new mutation, ENG c.1517T>C (p.Leu506Pro), in all patients and their mother. We suspect that HHT in these patients may be associated with this ENG mutation. Keywords: Hereditary hemorrhagic telangiectasia, Osler-Weber-Rendu disease, Pulmonary arteriovenous malformation